Penggunaan Pendekatan Konstruktivis Dalam Pembelajaran Tematik Di Sekolah Dasar - GUSFAYATI, RIKA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research was to improve the students’ learning achievement in thematic learning by using construktivism approach in grade III of SDN 18 Koto Tangah Kecamatan Tilatang Kamang.This was a Classroom Action Reseach which applied both qualitative and quantitative approaches.The subject of the research was the teacher and the student in grade III of SDN 18 Koto Tangah.The instruments of the research were test and observation sheet.The result of the research indicated that the students’ learning achievement improved from 75.32 in cycle I to 86.75 in cycle II.Thus, the use of constructivism approach could increase the students’ learning achievement.     Key term: constructivism approach, thematic learning, elemantary school students